War horse - Morpurgo, Michael (Scholastic, 2010)
World War I has started and the military needs horses to move equipment, charge the enemy, and carry wounded soldiers off the battlefield. Joey, a farm horse is sold to the Army. Joey misses the farmer's son, Albert, and spends the war years wondering if the war will ever end and if he will ever see Albert again.